The Impact of Digital Transformation in Human Resource Management on the Effectiveness of Private Vocational School Principals: Dampak Transformasi Digital pada Manajemen Sumber Daya Manusia terhadap Efektivitas Kepala Sekolah SMK Swasta - Pamela, Karim; Habibie, Dienha; Amin, Arip (Journal of Society and Development, 2025)
This study aims to explore the impact of digital transformation in human resource management (HRM) on the effectiveness of principals at private Vocational High Schools (SMKs) in Majalengka Regency. The method used is a quantitative approach with a survey design, where data were collected through questionnaires distributed to 35 principals. The results indicate that the implementation of information and communication technology (ICT) in HRM has improved the effectiveness of principals, with an average effectiveness score of 4.2 on a scale of 1 to 5. However, challenges such as a lack of training and adequate infrastructure remain obstacles in the technology implementation. This study concludes that although digital transformation offers opportunities to enhance HRM, further efforts in training and infrastructure investment are necessary to optimize its benefits. Recommendations are provided to improve staff training and the development of technological infrastructure in private SMKs in Majalengka Regency.